Effects of Primary Blast Overpressure on Retina and Optic Tract in Rats - DeMar, James; Sharrow, Keith; Hill, Miya; Berman, Jonathan; Oliver, Thomas; Long, Joseph (Frontiers in Neurology, 2016)
Blast has been the leading cause of injury, particularly traumatic brain injury and visual system injury, in combat operations in Iraq and Afghanistan. We determined the effect of shock tube-generated primary blast on retinal electrophysiology and on retinal and brain optic tract histopathology in a rat model. The amplitude of a- and b- waves on the electroretinogram (ERG) for both right and left eyes were measured prior to a battlefield-simulation Friedlander-type blast wave and on 1, 7, and 14 days thereafter. Histopathologic findings of the right and left retina and the right and left optic tracts (2.8 mm post-optic chiasm) were evaluated 14 days after the blast. For two experiments in which the right eye was oriented to the blast, the amplitude of ERG a- and b-waves at 7 days post-blast on the right side but not on the left side was diminished compared to that of sham animals (P=0.005-0.01) Histopathologic injury scores at 14 days post-blast for the right retina but not the left retina were higher than for sham animals (P=0.01), and histopathologic injury scores at 14 days for both optic tracts were markedly higher than for shams (P < 0.0001). Exposure of one eye to a blast wave, comparable to that causing human injury, produced injury to the retina as determined by ERG and histopathology, and to both post-chiasmatic optic tracts as determined by histopathology. This model may be useful for analyzing the effect of therapeutic interventions on retinal damage due to primary blast waves.